Gambaran Perawat dalam Merawat Anak yang Menjalani Terapi Continuous Ambulatory Peritoneal Dialysis (CAPD) di Rumah Sakit Persatuan Gereja Indonesia (PGI) Cikini Jakarta - Iga Dewi Purnamawati; Krisna Yetti; Happy Hayati (Jurnal Persada Husada Indonesia, 2015)
Continuous Ambulatory Peritoneal Dialysis (CAPD) therapy is one of substitute for renal therapy. Children undergoing CAPD therapy show good survivability. The roles of nurses in the CAPD unit are integral to this success. This study used a qualitative descriptive phenomenological approach and included as participants seven nurses with experience in CAPD therapy in children. Data were collected through in-depth interviews and were analysed by the Collaizi method. The results identified six main tasks CAPD nurses perform: optimisation of therapy in children, coordination and collaboration with other health care providers, training families to apply CAPD therapy, facing various challenges while providing care, strategising care for each individual child, and dealing with their own attitudes and emotions. Procedures need to be optimised in a comprehensive manner to care for children receiving CAPD therapy.